(untitled) (Nóema, 2020)
From an historical point of view, the Italian reception of Whitehead’s philosophy of religion turns out to be defective and the last translation of Process and Reality is the occasion to fill these gaps. The evaluation of Whitehead’s position in the field of analytical philosophy of religion, the right contextualization of his thought and a critical interpretation of the fifth part of Process and Reality show that regarding Whitehead only as the father of process theology is rather reductive and even misleading. His legacy grows more fruitful considering the recent development of analytic philosophy of religion, with peculiar reference to his reflections on religious language and evil.